2017
DOI: 10.1002/jaba.369
|View full text |Cite
|
Sign up to set email alerts
|

Training kindergarten students lockdown drill procedures using behavioral skills training

Abstract: During situations in which a gunman is present on a school campus, lockdowns are initiated until the threat is removed. However, there are no data demonstrating an effective teaching strategy to increase students' correct responding during a lockdown. We evaluated the effectiveness of behavioral skills training (BST) to teach three groups of kindergarten students how to respond during lockdown drills. Results showed that participant groups displayed increases in correct steps and decreases in noise levels afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Other research has targeted traffic safety behaviors for drivers, passengers, and pedestrians (e.g., Austin et al, 1998;Austin et al, 2006;Crowley-Koch et al, 2011;Huybers et al, 2004;Van Houten, 1988;Van Houten & Nau, 1981, 1983Van Houten et al, 1985;Van Houten et al, 1980;Van Houten & Retting, 2001;Van Houten & Rolider, 1988;VanWagner et al, 2011;Yeaton & Bailey, 1978, 1983, with safety-belt use being a common target. Finally, ABA research has also addressed gun safety (e.g., Gross et al, 2007;Himle et al, 2004;Miltenberger et al, 2004;Miltenberger et al, 2005), child safety (Carrow et al, 2020;Dancho et al, 2008;Dickson & Vargo, 2017;Himle & Wright, 2014;Jones et al, 1981;Mathews et al, 1987;Peterson, 1984), and safe sex (Carrigan et al, 1995;Honnen & Kleinke, 1990;Montesinos et al, 1990). Most of these studies employed behavioral skills training or component packages (Montesinos et al, 1990;Peterson, 1984) and others used antecedent interventions involving prompts (e.g., Austin et al, 1998;Austin et al, 2006;Carrigan et al, 1995;Crowley-Koch et al, 2011;Honnen & Kleinke, 1990).…”
Section: Applied Behavior Analysis and Public Healthmentioning
confidence: 99%
“…Other research has targeted traffic safety behaviors for drivers, passengers, and pedestrians (e.g., Austin et al, 1998;Austin et al, 2006;Crowley-Koch et al, 2011;Huybers et al, 2004;Van Houten, 1988;Van Houten & Nau, 1981, 1983Van Houten et al, 1985;Van Houten et al, 1980;Van Houten & Retting, 2001;Van Houten & Rolider, 1988;VanWagner et al, 2011;Yeaton & Bailey, 1978, 1983, with safety-belt use being a common target. Finally, ABA research has also addressed gun safety (e.g., Gross et al, 2007;Himle et al, 2004;Miltenberger et al, 2004;Miltenberger et al, 2005), child safety (Carrow et al, 2020;Dancho et al, 2008;Dickson & Vargo, 2017;Himle & Wright, 2014;Jones et al, 1981;Mathews et al, 1987;Peterson, 1984), and safe sex (Carrigan et al, 1995;Honnen & Kleinke, 1990;Montesinos et al, 1990). Most of these studies employed behavioral skills training or component packages (Montesinos et al, 1990;Peterson, 1984) and others used antecedent interventions involving prompts (e.g., Austin et al, 1998;Austin et al, 2006;Carrigan et al, 1995;Crowley-Koch et al, 2011;Honnen & Kleinke, 1990).…”
Section: Applied Behavior Analysis and Public Healthmentioning
confidence: 99%
“…Over the past 15 years, a growing body of research has shown BST to be an effective teaching model for individuals with disabilities (Ledbetter‐Cho et al., 2019; Thomas, Lafasakis, & Spector, 2016), young children (Dickson & Vargo, 2017; Tai & Miltenberger, 2017), college students (Hankla, Kohn, & Normand, 2018; Stocco, Thompson, Hart, & Soriano, 2017), parents or caregivers (Conklin & Wallace, 2019; Dogan et al., 2017), and educators (Hogan, Knez, & Kahng, 2015; Lerman et al., 2019). Skills taught during BST for educators have included learning the picture exchange communication system (PECS; Homlitas, Rosales, & Candel, 2014), discrete trial teaching, incidental teaching, and activity schedules (Fetherston & Sturmey, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Experiment 3 was designed to train children to avoid touching packages they found on school property, leave the area, and tell an adult what they found. This behavioral chain has been taught to young children regarding gun safety (e.g., Miltenberger et al, 2005) as well as poison, lighter, and abduction safety (e.g., Vanselow & Hanley, ), and lockdown drill procedures (Dickson & Vargo, ).…”
Section: Resultsmentioning
confidence: 99%